Didactical Obstacles for Junior High School Students in Post-Pandemic Mathematics Learning - Kulsum, Zulfa; Amelia, Risma (IKIP Siliwangi, 2024)
Face-to-face learning has been re-implemented by several schools after 2 years offline, and this has caused several obstacles when implementing it. Especially mathematics learning, which tends to require more effort to deliver material. Post-pandemic learning causes didactical obstacles to student and teacher learning during the teaching and learning process. So the purpose of this study is to analyze student barriers to post-pandemic learning. The research method used in this study is qualitative-descriptive, with data collection techniques such as survey methods, observation results, questionnaires, and interviews. The object of this study was 19 grade VIII–4 students and senior teachers at SMP Negeri 1 Cihampelas. This research uses several instruments for students, and the results can be analyzed for obstacles to the post-pandemic learning process. Based on the results of the study, it shows that post-pandemic learning barriers for Grade VIII–4 students are adaptation to a new environment; understanding the material is more difficult and ineffective because the learning process does not involve technology, conventional learning methods, psychological changes, or habits when online learning is still carried over so that it affects face-to-face learning, where students are not ready to get the next material due to the material they previously did not understand due to the lack of maximum understanding of students when learning online. Not only students, but teachers also have their own obstacles when learning after this pandemic, so teachers also need time to be able to adapt to face-to-face meetings that run according to mutual expectations.